Evaluation of amplified ribosomal DNA restriction analysis (ARDRA) and species-specific PCR for identification of Bifidobacterium species - Krízová, Jana; Spanová, Alena; Rittich, Bohuslav (Systematic and applied microbiology, 2006)
Molecular biological methods based on genus-specific PCR, species-specific PCR, and amplified ribosomal DNA restriction analysis (ARDRA) of two PCR amplicons (523 and 914bp) using six restriction enzymes were used to differentiate among species of Bifidobacterium. The techniques were established using DNA from 16 type and reference strains of bifidobacteria of 11 species. The discrimination power of 914bp amplicon digestion was higher than that of 523bp amplicon digestion. The 914bp amplicon digestion by six restrictases provided unique patterns for nine species; B. catenulatum and B. pseudocatenulatum were not differentiated yet. The NciI digestion of the 914bp PCR product enabled to discriminate between each of B. animalis, B. lactis, and B. gallicum. The reference strain B. adolescentis CCM 3761 was reclassified as a member of the B. catenulatum/B. pseudocatenulatum group. The above-mentioned methods were applied for the identification of seven strains of Bifidobacterium spp. collected in the Culture Collection of Dairy Microorganisms (CCDM). The strains collected in CCDM were differentiated to the species level. Six strains were identified as B. lactis, one strain as B. adolescentis.
Keywords: DNA, Ribosomal Spacer; RNA, Ribosomal, 16S; DNA, Bacterial; Sequence Alignment; polymerázová řetězová reakce; Polymerase Chain Reaction; polymorfismus délky restrikčních fragmentů; RNA, Ribosomal, 23S; Bifidobacterium; DNA bakterií; Base Sequence; sekvence nukleotidů; RNA ribozomální 16S; Humans; Polymorphism, Restriction Fragment Length; fylogeneze; RNA ribozomální 23S; Species Specificity; druhová specificita; Phylogeny; sekvenční seřazení; mezerníky ribozomální DNA; lidé